Flexibility through working time accounts : reconciling economic efficiency and individual time requirements - Hartmut Seifert (Hans-Böckler-Stiftung, Wirtschafts- und Sozialwissenschaftliches Institut (WSI), 2004)
This paper discusses the tension between the demands of economic efficiency, on the one hand, and non-economic ends (leisure, family, etc.) on the other. It starts by outlining the formative characteristics of flexible forms of working time to then investigate the regulatory structures of working time accounts (Part 3). The argument of relative predominance of economic aspects against private time needs is then examined further. Possible conflicts between goals and uses of the flexible organisation of time are then discussed.
Keywords: 330